Pengaruh Kualitas Pelayanan, Persepsi Harga, Cita Rasa Terhadap Kepuasan Konsumen Mie Gacoan - Nada Lina Hanim; Hadi Sunaryo; Ita Athia (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to describe service quality, price perception, taste, customer satisfaction and analyze the effect of service quality, price perception, taste on consumer satisfaction of Mie Gacoan. The method of data collection in this study was done by distributing online questionnaires using snowball sampling. The sample used in this study were 91 students of the Faculty of Business Economics, Islamic University of Malang, Class of 2018 from the management, accounting, and Islamic banking study programs. The results showed that simultaneously the variables of service quality, price perception, and taste had a positive and significant effect on consumer satisfaction of Mie Gacoan. The results of this study also found that service quality variables affect customer satisfaction. The price perception variable was found to have an effect on consumer satisfaction. The taste variable was found to have an effect on consumer satisfaction. Keywords: Service Quality, Price Perception, Taste, and Consumer Satisfaction